Pathogenesis and pathophysiological mechanism of obstructive sleep apnea: a review of anatomical, cytoskeletal, muscular, and neurological abnormalities / Siti Nuraidatul Amira - Amira, Siti Nuraidatul; Mansor, Masaany; Abdul Rahim, Norazila; Kamarudin, Intan Kartika; Palanisamy, Vanitha; Mohamad, Mariam; Omar, Effat (Faculty of Medicine, 2025)
Introduction: Obstructive sleep apnea (OS) af f ects approximately 1 billion people globally. It leads to signif icant morbidity and mortality, causing a signif icant burden on the healthcare system. Collapse of the upper airway during sleep is the main pathology in OSA. The aim of this review is to update OSA' s pathogenesis and pathophysiological mechanisms, f ocusing on microanatomical f eatures, including neuronal and muscular morphological abnormalities. Results: OSA patients have smaller maxilla and mandible, longer, thicker sof t palate, and larger tongue. Microscopically, the upper airway in these patients shows increased variability in muscle f iber size and f orm due to concurrent hypertrophy and atrophy. The muscular layer is also inf lamed, reducing its contractility and f unctionality. Immunohistochemistry shows that OSA patients’ upper airway muscles lack desmin expression, impairing mitochondria placement and, thus, decreasing muscular oxidative activity. Neurologically, OSA patients were reported to have abnormalities of the large, small, motor, sensory, myelinated, and myelinated nerves of the palate and pharynx. Axon density and diameter are reduced. An increased number of regenerating nerves is ref lected in increased GAP43 protein, indicating nerve injury. Conclusion: OSA is associated with macro and microscopic abnormalities involving the muscles and nerves of the patient' s upper airway.